2022
DOI: 10.3389/fcimb.2022.772829
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and Evolutionary Analysis of Salmonella enterica Serovar Kentucky Sequence Type 198 Isolated From Livestock In East Africa

Abstract: Since its emergence in the beginning of the 90’s, multidrug-resistant (MDR) Salmonella enterica subsp. enterica serovar Kentucky has become a significant public health problem, especially in East Africa. This study aimed to investigate the antimicrobial resistance profile and the genotypic relatedness of Salmonella Kentucky isolated from animal sources in Ethiopia and Kenya (n=19). We also investigated population evolutionary dynamics through phylogenetic and pangenome analyses with additional publicly availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Kentucky ST198 became the second most prevalent serotype (3.10% [13/420 strains]) in the production chain of broiler chickens in Sichuan Province, China ( 13 ). It has also been increasingly detected in animals and clinics in countries outside China, e.g., India (3.49% in animals and 0.31% in patients), East Africa, Spain, and Switzerland ( 16 19 ).…”
Section: Resultsmentioning
confidence: 99%
“…Kentucky ST198 became the second most prevalent serotype (3.10% [13/420 strains]) in the production chain of broiler chickens in Sichuan Province, China ( 13 ). It has also been increasingly detected in animals and clinics in countries outside China, e.g., India (3.49% in animals and 0.31% in patients), East Africa, Spain, and Switzerland ( 16 19 ).…”
Section: Resultsmentioning
confidence: 99%
“…The presence of C63PI (six/six) and SPI 9 (six/six) was noticed herein in all S. Mbandaka genomes. Although SPIs 1-5 are common in Salmonella serovars [ 46 ], there are divergences regarding the presence and absence of genes in these islands [ 45 , 47 ]. Many of those mainly found in SPI 2 encode structural and effector proteins of a type III secretion system (T3SS) that transfer essential virulence effectors with important functions during cell infection [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…SPI 3 harbours the mgtCB virulence genes that are related to Mg 2+ uptake when under restricted availability of this cation, such as within the macrophage environment [ 45 , 51 ]. While the mgtCB genes were predicted in S. Mbandaka isolates, other regions of SPI 3 were absent in all the genomes [ 47 ], possibly implying that these genes are not essential for Salmonella serovar infection. Although the expressions of virulence genes are not the focus of this work, we acknowledge that additional research into the variation in the virulence factors and the interaction of those genes will further our understanding of the role of the virulence mechanism in this serovar and contribute valuable insights into the broader landscape of Salmonella pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In Europe, human Kentucky-II cases (ST198) are often linked to international travel [62]; however, studies have shown that this lineage is expanding significantly in poultry flocks in Europe [33, 63, 64]. More recently, ST198 isolates (Kentucky-II) have been found in cattle and also swine in Africa [65]. Furthermore, of the ten SNP clusters with multiple source types that belong to the Kentucky-II lineage, isolates from seven of them were only found in cattle and humans.…”
Section: Discussionmentioning
confidence: 99%